COVID‐19 shines a light on health inequities in communities of color: A youth‐driven photovoice inquiry. Issue 8 (20th April 2022) - Augsberger, Astraea; Toraif, Noor; Young, Adrienne; Dimitri, Noelle C.; Bautista, Rosaylin; Pierre, Ja'Karri; Le, Catherine; Idahor, Osasenaga; Jusme, Calvin; Gergen Barnett, Katherine A.
Abstract: This manuscript reports on a youth‐driven health assessment engaging youth of color in identifying community health priorities during the coronavirus disease 2019 (COVID‐19) pandemic. Photovoice, a participatory visual ethnographic health assessment strategy, was used to explore the question: What does health or healthiness mean to you and/or your community? Youth captured images that represented their priorities. The photos were discussed using the SHOWed framework and analyzed thematically. Four themes related to community health were identified. Additionally, youth captured their narrative of COVID‐19 as "a revealing force that highlights systemic inequities, driving individuals and communities to both cultivate their resilience and take healthcare into their own hands in response to government and policy level failures." Youth are acutely aware of the historical and structural inequities that create multi‐level barriers to healthcare access. Health inequities existed long before the pandemic, but the current crisis requires us to examine ways to transform the healthcare landscape moving forward.